What do we know about post-conflict transitional justice from academic research: key insights for practitioners - Charlotte Fiedler; Karina Mross (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Societies that have experienced violent conflict face considerable challenges in building sustainable peace. One crucial question they need to address is how to deal with their violent past and atrocities that were committed – for example, whether perpetrators should be held accountable by judicial means, or whether the focus should be laid on truth telling and the compensation of victims. Transitional justice (TJ) offers a range of instruments that aim to help societies come to terms with their history of violent conflict. Systematic, empirical analyses of TJ instruments have been emerging over the last years. This Briefing Paper summarises the policy-relevant insights they provide regarding the main TJ instruments: trials; truth commissions; reparations for victims; and amnesties. Reviewing academic literature on the effects of transitional justice in post-conflict contexts, three main messages emerge: Initial evidence suggests that transitional justice can help to foster peace. Contrary to concerns that actively dealing with the past may deepen societal divisions and cause renewed conflict, most statistical studies find either positive effects or no effects of the various instruments on peace. Research indicates that amnesties can help to build peace, though not as a response to severe war crimes. Contrary to strong reservations against amnesties at the international level (especially on normative grounds), several academic studies find that amnesties can statistically significantly reduce the risk of conflict recurrence. However, the most extensive and recent study also shows that this effect varies depending on the context: amnesties can contribute to peace when they are included in peace agreements, but have no effect after episodes of very severe violence. To effectively foster peace, trials should target all perpetrators involved in the conflict, not only the defeated party. A likely explanation for this finding from a recent study is that otherwise domestic trials can be used by the victorious party to punish and repress the defeated side. More generally, donors should be aware that if a political regime is able to instrumentalise a transitional justice process, for instance after a one-sided victory or in an undemocratic environment, the process is often not conducive to peace. Reviewing the literature also makes clear that important, open questions remain: Can transitional justice contribute to a deeper quality of peace that goes beyond the absence of violence? TJ should be able to foster reconciliation and mend broken societal relationships. However, if and how TJ can affect social cohesion after conflict needs to be better understood. How do various transitional justice instruments need to be combined? Both the academic literature and policy documents suggest that it is important to find the right mix of instruments, but more systematic analyses of successful combinations of TJ instruments are necessary. What role does donor support play in processes of transitional justice? Although transitional justice can be strongly domestically driven, such as in Colombia, donor funding often facilitates these processes. However, we still know too little about the effectiveness of such support.
Keywords: 330; Sicherheit; Frieden und fragile Staaten; Soziale Kohäsion